Association between Exposure to Particulate Matter during Pregnancy and Multidimensional Development in School-Age Children: A Cross-Sectional Study in Italy - Paolo Girardi (MDPI AG, 2021)
Air pollutants can potentially affect the development of children. However, data on the effect of exposure to air pollution during pregnancy and developmental outcomes in school children are rare. We investigated the link between prenatal exposure to particulate matters smaller than 10 microns (PM10) and the development of school-age children in multiple domains. Cross-sectional data were collected in Italy between 2013 and 2014. Children aged between 5 and 8 years (n = 1187) were assessed on cognitive, communication, socio-emotional, adaptive, and motor developmental domains using the Developmental Profile 3 questionnaire. The monthly average concentration of PM10 during the entire fetal period was linked to the municipality of residence of the children. The increase in the prenatal PM10 was associated with a decrease in the cognitive score during the second (+13.2 µg/m3 PM10 increase: −0.30 points; 95%CI: −0.12–−0.48) and third trimesters of pregnancy (−0.31 points; 95%CI: −0.11–−0.50). The communicative domain was also negatively influenced by PM10 increases in the second trimester. The development of cognitive and communicative abilities of children was negatively associated with the exposure to PM10 during the period of fetal development, confirming that exposure to air pollution during pregnancy can potentially hinder the development of the brain.